Single Pd atoms supported on ultra-thin bismuth tungstate nanosheets with oxygen vacancies as an efficient photocatalyst. Issue 4 (4th January 2023) - Hu, Lizhen; Huang, Xiaoxiang; Nie, Qianqian; Wang, Teng; Liu, Penglei; Liu, Jiayou; Tan, Zhongchao; Yu, Hesheng
Abstract : The O vacancies of ultra-thin bismuth tungstate confine Pd atoms to produce a Pd-VO -UBWO SAC, which exhibits high photocatalytic activity for NO oxidation and RhB degradation. Abstract : Efficient and highly selective photocatalysts for NO oxidation remain a great challenge. In this work, single Pd atoms are deposited onto ultrathin bismuth tungstate (UBWO) nanosheets with O vacancies (Pd-VO -UBWO) by an impregnation combined with calcination method for the first time. The Pd-VO -UBWO catalysts exhibit efficient and highly selective photocatalytic activity for the degradation of NO. At a NO inlet concentration of 48 ppm, the NO conversion rate using the Pd-VO -UBWO catalyst is 89.5% within 1 h of visible light irradiation, which is much higher than that of VO -UBWO (45.7%). Its selectivity for NO conversion to NO3 − ions is 78.5%. Moreover, experimental results show that the introduction of single Pd atoms promotes the generation of O2 ˙ − and OH˙. Density functional theory calculations indicate that single Pd atoms favor the adsorption and activation of NO on the Pd-VO -UBWO surface, thus boosting the effective conversion of NO. Furthermore, the Pd-VO -UBWO catalyst can achieve higher degradation efficiency of Rhodamine B (86.9%) in liquid solution than VO -UBWO (68.8%).